2016
DOI: 10.1021/acs.chemrev.6b00430
|View full text |Cite
|
Sign up to set email alerts
|

2,2′-Bipyrrole-Based Porphyrinoids

Abstract: A large number of porphyrinoids containing 2,2'-bipyrrole subunits have appeared since they were originally found as a component of sapphyrin and corrole, and it was found that the bipyrrole subunit endowed macrocycles with specific geometric features and electronic properties. Synthetic methods for bipyrrole-containing precursors for porphyrinoid are summarized in this review; these include coupling reactions of pyrrole rings, pyrrole ring-forming reactions leading directly to bipyrrole units, and synthetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 221 publications
0
47
0
4
Order By: Relevance
“…A perusal of literature revealed that Berlin and Breitmaier in 1994 reported the first example of pyridine containing porphyrinoids and ever since several interesting pyridine incorporated porphyrinoids that includes regular,, , , , contracted, expanded, , , and heteroporphyrinoids were reported. Thus, several very stable pyridine and bipyridine, , containing porphyrinoids are reported in recent times and explored their structural, spectral and coordination properties. Recently, we reported synthesis of series m ‐benzihexaphyrins (1.0.0.1.1.1) 1 and studied their properties.…”
Section: Introductionmentioning
confidence: 99%
“…A perusal of literature revealed that Berlin and Breitmaier in 1994 reported the first example of pyridine containing porphyrinoids and ever since several interesting pyridine incorporated porphyrinoids that includes regular,, , , , contracted, expanded, , , and heteroporphyrinoids were reported. Thus, several very stable pyridine and bipyridine, , containing porphyrinoids are reported in recent times and explored their structural, spectral and coordination properties. Recently, we reported synthesis of series m ‐benzihexaphyrins (1.0.0.1.1.1) 1 and studied their properties.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57][58][59][60][61] Sapphyrins containing four meso-aryl substituentsc an serve as favorable building blocks fort he further designo fm olecules, which are similar to meso-aryl-substituted porphyrins, whose redox properties and chemicalr eactions can be finely tuned. [15,57,58,60,61] Open-chainp entapyrroles (or pentapyrrotetramethenes) with meso-tetraaryl substituents were first isolated as the majors ide productsi nt he synthesis of corrolew ith ah igh yield (11%,t he same as the target product), [62] and later attracted greater attention as synthetic precursors for the respective sapphyrins. [15,57,58,60,61] Open-chainp entapyrroles (or pentapyrrotetramethenes) with meso-tetraaryl substituents were first isolated as the majors ide productsi nt he synthesis of corrolew ith ah igh yield (11%,t he same as the target product), [62] and later attracted greater attention as synthetic precursors for the respective sapphyrins.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and anion binding properties of a number of these systems were reviewed in a book chapter by Maeda [29]. Aryl-bridged bispyrroles have also been used extensively as building blocks in the construction of macrocycles [11] and for preparing low molecular weight compounds with membrane permeability [58]. A full summary of this work is not possible here.…”
Section: Aryl- and Diketone-bridged Bispyrrole-based Anion Receptorsmentioning
confidence: 99%
“…In 1996, the non-conjugated tetrapyrrolic macrocycle, calix[4]pyrrole, functioned as a neutral anion receptor (Figure 1) [10]. Expanded porphyrins [11,12], calixpyrroles [13] and their macrocyclic analogues [14,15] have been extensively reviewed in the context of anion and ion pair recognition. In this review we focus on the anion binding properties of neutral and charged acyclic pyrrolic systems.…”
Section: Introductionmentioning
confidence: 99%